EVALUATION OF PERIAPICAL AREA IN ROOT-FILLED TEETH WITH PERIAPICAL LESIONS: A CBCT STUDY - Mihaela Sălceanu; Cristina Dascălu; Cristi Giuroiu; Tudor Hamburda; Cristina Antohi; Corina Concita; Claudiu Topoliceanu; Georgiana-Andreea Frumuzache; Alice-Teodora; Anca Melian (Romanian Society of Oral Rehabilitation, 2024)
The aim of this study is to investigate the possibilities of diagnosis and post-treatment monitoring of chronic periapical lesions. Materials and method. The cross-sectional study included 151 patients (gender: 52 males, 99 females; mean age 48.36 ± 15.708 yrs.) with 391 root-filled teeth (mean follow-up of 5.25 +/- 1.759 yrs.). Clinical examination and radiographic assessment of the root and its periapical area were performed to evaluate its status by PAI-CBCT score. Patients were included in the treatment within the Clinical Education Base "M. Kogălniceanu" of the Faculty of Dentistry, U.M.F. "Grigore T.Popa" Iaşi. CBCT images were obtained using PaX-Uni3D (TVAPANO04, VATECH). The dimensions of periapical lesions in coronal-apical, mesial-distal and buccal-oral sections were measured using the Ez3D 2009 Plus software application. CBCT parameters were set for 20 second exposure time, 85 kV, 5mA. The mean values ​​of the CBCT-PAI index were recorded. Results. Apical periodontitis was diagnosed in 181 endodontically treated teeth, corresponding to a 46,3% prevalence of periapical lesions. The distribution of CBCT-PAI indices was as follows: CBCT-PAI 3 40%, followed by CBCT-PAI 2 40%, CBCT-PAI 4 20%, and CBCT-PAI 5 20%. Conclusion. The most frequent CBCT-PAI score was 3 recorded in 40% of the root-filled teeth. CBCT examination and CBCT-PAI index are precise, reliable and reproducible tools in the evaluation of the post-treatment evolution of the chronic periapical lesions.